2017
DOI: 10.1186/s12886-017-0417-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute angle closure attack after an intravitreal bevacizumab injection for branch retinal vein occlusion: a case report

Abstract: BackgroundIntravitreal injection is widely used to treat retinal vein occlusion, and acute angle closure (AAC) is an exceptional complication of intravitreal injection. The authors report a case of AAC that occurred immediately after administering intravitreal bevacizumab to treat branch retinal vein occlusion (BRVO).Case presentationA 65-year-old woman was referred to the retina clinic of a tertiary referral center for the treatment of macular edema secondary to BRVO. On slit lamp examination, anterior chambe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…In most cases, intraocular pressure (IOP) elevation after an intravitreal injection appears as a transient IOP spike due to volume effects in the closed intravitreal cavity. However, IOP elevation due to morphological changes in the anterior chamber (AC) angle has been rarely reported [ 3 , 4 ]. We report a case of acute angle closure (AAC) refractory to mannitol and laser iridotomy that occurred after intravitreal bevacizumab (IVB) injection in an eye for treatment of central retinal vein occlusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, intraocular pressure (IOP) elevation after an intravitreal injection appears as a transient IOP spike due to volume effects in the closed intravitreal cavity. However, IOP elevation due to morphological changes in the anterior chamber (AC) angle has been rarely reported [ 3 , 4 ]. We report a case of acute angle closure (AAC) refractory to mannitol and laser iridotomy that occurred after intravitreal bevacizumab (IVB) injection in an eye for treatment of central retinal vein occlusion.…”
mentioning
confidence: 99%
“…Jeong et al [ 3 ] and Semoun et al [ 4 ] previously reported AAC after IVB. In these cases, the eyes were hyperopic and showed shallow AC at baseline, accounting for the risk of AAC.…”
mentioning
confidence: 99%
“…When this happens, in many cases AC paracentesis is necessary to avoid permanent damage to the optic nerve. Persistent IOP increase may be present in some eyes and may cause acute angle closure attack [4].…”
Section: Intravitreal Injections and Acute Increase Of Intra-ocular Pmentioning
confidence: 99%
“…There is some controversy about the clinical management of IOP increase in the post-intravitreal injection period [4]: while some reports showed a rapid IOP spike [5] and speculated that this might cause damage to the optic nerve, other authors believe this is negligible as IOP usually returns to normal within 15–30 min [6]. Nevertheless, there are patients with considerable IOP spikes of more than 80 mmHg post intravitreal injection that might be asymptomatic and therefore undetected after the injection or at the next day clinical check-up [7], which might result in serious and irreversible damage to the optic nerve and should have been treated immediately.…”
Section: Intravitreal Injections and Acute Increase Of Intra-ocular Pmentioning
confidence: 99%
“…Intravitreal injection (IVI) of anti-vascular endothelial growth factor (anti-VEGF) is widely used for the treatment of various retinal pathologies such as neovascular age-related macular degeneration, 1,2 diabetic macular edema, 3 and retinal venous occlusion. 4 Although IVI is a safe procedure, complications have been reported, including acute angle closure 5 and…”
Section: Introductionmentioning
confidence: 99%